Genesis of Instrumentation in Interaction with the Geoboard: An Experience in the PARFOR of Mathematics Teaching Degree - Silva Feitosa, Francisco Eteval (2024)
This paper presents partial results of a Post-Doctoral research at the Post-Graduate Program in Science and Mathematics Education at UFPE. In this section, we analyze the Instrumental Genesis of the manipulable material Geoboard in situations involving the mathematical object Polygons. For that, we did a training workshop, using the Geoboard, for Mathematics teachers being trained by the National Program for the Training of Basic Education Teachers (PARFOR). The underlying theoretical framework is the Instrumental Approach and Instrumental Orchestration. With a qualitative approach and an action-research design, data were collected from observations, questionnaires and audio-visual records and analyzed in the light of the Instrumental Activity Situations (SAI), model proposed by Pierre Rabardel. The results indicate that the instrumental genesis of the Geoboard did not occur and indicate that the instrumentalization process needs more time and involves concepts in action that are relevant to the situations that will be proposed. Furthermore, limitations in the content knowledge of the participants may have limited the rules of action and consequently the schemes developed.